Recycled Tire as Base Isolator for Low Rise Building in Malaysia - Yun Tong, Siow; Kasa, Anuar; Aminah Osman, Siti (International Journal of Engineering and Technology, 2019)
The main goal of isolation is to provide lateral flexibility to building foundation in order to mitigate horizontal movement resulted from earthquake event. Conventional seismic isolation system consists of elastomeric or sliding system which is costly. Recycled Tire Isolator (RTI) is a model designed to be installed at building foundations to resist earthquake forces. It is laterally flexible and has some similarities compared with commercial base isolators.RTIwas fabricated using tread sections of recycled tires which are cut into pads of 300mm x 210mm and each pad has thickness of 10mm. Adhesive was applied on the cut tire pads before they were stacked on top of each other. Pressure was imposed on theRTIto ensure the layer of pads stick well. Static compression test and dynamic load test were conducted to examine the dynamic and mechanical properties ofRTI. In static compression test, a controlled axial load of 380 kN (maximum capacity of the compression test machine) was applied on to theRTI. A displacement of 12.2mm was recorded. For dynamic load test, Servo Hydraulic MTS322 Testing Machine was used. The dynamic stiffness, damping ratio and damping coefficient were obtained and compared with the commercial isolator.Â Â Â